Aorta and brachiocephalic artery pathology in dyslipidemia - B. M. Lipovetsky (Российский кардиологический журнал)
Aorta and brachiocephalic artery atherosclerosis in various types of dyslipidemia (DLP) were examined. Twenty-six participant demonstrated combination of aortic and coronary or cerebral atherosclerosis: 5 patients had aortic isthmus stenosis, 8 -abdominal aortic aneurysm, 8 - bifurcation stenosis, 9 - carotid artery stenosis. Abdominal aortic aneurysm, aorta isthmus stenosis, and bifurcation stenosis were typical for familial hypercholesterolemia, carotid artery stenosis - for hypertriglyceridemia, or very low levels of high-density lipoprotein cholesterol (HDL CH). During 6-10 years of follow-up, among 21 patients (other 9 had dropped out), 6 patients died, and 9 patients underwent surgery: aortic or carotid intervention (n=3 and 6, respectively). Patients with DLP require aggressive treatment with statins orfibrates, according to DLP type, and continuous Doppler ultrasound monitoring of aorta and carotid artery morphology.